The distribution of the product of two independent generalized trapezoidal random variables. Issue 21 (1st November 2016) - Garg, Mridula; Sharma, Ajay; Manohar, Pratibha
ABSTRACT: In this article, we derive the probability density function (pdf) of the product of two independent generalized trapezoidal random variables having different supports, in closed form, by considering all possible cases. We also show that the results for the product of two triangular and uniform random variables follow as special cases of our main result. As an illustration, we obtain pdf of product for a suitably constrained set of parameters and plot some graphs using MATLAB, which express variation in pdf with change in different parameters of the generalized trapezoidal distribution.